2009
DOI: 10.1186/1471-2458-9-66
|View full text |Cite
|
Sign up to set email alerts
|

Community-based infant hearing screening in a developing country: parental uptake of follow-up services

Abstract: Background: Universal newborn hearing screening is now considered an essential public health care for the early detection of disabling life-long childhood hearing impairment globally. However, like any health interventions in early childhood, parental support and participation is essential for achieving satisfactory uptake of services. This study set out to determine maternal/infant sociodemographic factors associated with follow-up compliance in community-based infant hearing screening programmes in a develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
31
0
2
Order By: Relevance
“…This failure to remind and encourage caregivers to comply with the recommended follow-up re-test may have affected follow-up rates adversely [18]. Lack of quality control and inefficient tracking of caregivers following discharge [9,11], as well as inadequate support from other health care professionals are reasons which have been offered for the poor follow-up rates in studies conducted in the private health sector in South Africa [9,11].…”
Section: Sd) Testing Younger Newborns Predisposed As They Are To Rementioning
confidence: 99%
See 2 more Smart Citations
“…This failure to remind and encourage caregivers to comply with the recommended follow-up re-test may have affected follow-up rates adversely [18]. Lack of quality control and inefficient tracking of caregivers following discharge [9,11], as well as inadequate support from other health care professionals are reasons which have been offered for the poor follow-up rates in studies conducted in the private health sector in South Africa [9,11].…”
Section: Sd) Testing Younger Newborns Predisposed As They Are To Rementioning
confidence: 99%
“…Internationally, high referral rates and sub-par follow-up return rates were also reported for hospital-based (32.3% and 16% respectively) and immunization clinic-based (14.3% and 48.1% respectively) NHS programs in Nigeria [17,18]. A review of the average coverage and follow-up return rates across a combination of 46 developed and developing countries indicated that regional coverage (66% for high income and 1% for low income countries) falls significantly below proposed benchmarks (≥95%) [15], with only the high income countries achieving follow-up rates above these benchmarks (≥70%) [15,21].…”
Section: Sd) Testing Younger Newborns Predisposed As They Are To Rementioning
confidence: 99%
See 1 more Smart Citation
“…Poor uptake after the initial failed screening test has also been attributed to minimal or no prompting by screening staff, caregivers not being traceable, and the perception that hearing loss is not life-threatening. 43,100 Financial and logistical constraints…”
Section: Poor or Inadequate Information From Health Care Providersmentioning
confidence: 99%
“…Hal ini sesuai dengan studi yang dilakukan oleh Prince dkk 18 yang menemukan bahwa bayi dari ibu yang tidak menyelesaikan sekolah menengah atas mempunyai kecenderungan untuk tidak menyelesaikan tahapan skrining pendengaran yang dibutuhkan oleh bayinya. 18,19 Kami juga menemukan bahwa kesadaran ibu akan pentingnya deteksi dini gangguan pendengaran dan intervensi segera sangat mempengaruhi keberhasilan program skrining. Untuk meningkatkan kesadaran ibu, perlu diberikan edukasi mengenai manfaat dan pentingnya skrining pendengaran sebelum pulang dari perawatan Perinatologi.…”
Section: Pembahasanunclassified